2019
DOI: 10.1097/cej.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in Mozambique in 2015–2016: data from the Maputo Central Hospital Cancer Registry

Abstract: There is scarce information on cancer incidence in Mozambique. We aimed to describe cancer incidence data from the Cancer Registry of the Maputo Central Hospital (MCH) in 2015-2016, for Maputo City dwellers, and to compare the incidence rates with those observed in 1956-1961. Cancers with incidence data in 2015-2016 were identified by the Cancer Registry of the MCH. Crude and age-standardized incident rates (ASIR, per 100 000) - direct method, world standard population - were computed for Maputo City, under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…7 In Mozambique, cervical cancer is reported to be the most common cancer among women, and was responsible for 45.5% of all cancer-related deaths in 2014, reflecting the high prevalence of both HPV and HIV infections. 18 Furthermore, in 2018 it was estimated that 8.5 million women aged 15 years and older are at risk of developing cervical cancer in Mozambique. 7 Self-sampling testing might be a low-resource alternative to physiciansampling to detect HPV DNA with similar sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In Mozambique, cervical cancer is reported to be the most common cancer among women, and was responsible for 45.5% of all cancer-related deaths in 2014, reflecting the high prevalence of both HPV and HIV infections. 18 Furthermore, in 2018 it was estimated that 8.5 million women aged 15 years and older are at risk of developing cervical cancer in Mozambique. 7 Self-sampling testing might be a low-resource alternative to physiciansampling to detect HPV DNA with similar sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, HPV DNA testing has higher detection sensitivity as compared with visual inspection with acetic acid (VIA), the national strategy adopted for cervical cancer screening in Mozambique. 18,20,21 Therefore, HPV DNA testing might be a better primary screening method for cervical cancer prevention in low-resource countries. 22,23 Currently, three licensed HPV vaccines are available: bivalent (Cervarix ® ; GSK, Rixensart, Belgium), quadrivalent (Gardasil ® ; Sanofi Pasteur MSD, Lyon, France), and nonavalent (Gardasil 9 ® ; Sanofi Pasteur MSD, Lyon, France).…”
Section: Introductionmentioning
confidence: 99%
“…Mozambique has a high rate of EC. According to previous studies, EC is the 4 th most incident malignant tumor in Maputo in both genders [8]. A study of 522 consecutive cases of EC diagnosed and treated at the Maputo Central Hospital revealed that most patients were female (n=291, 55.7%), and born in the southern region of the country (n=418, 80.1%) where the consumption of maize in food and in fermented beverages is high [9].…”
Section: Essaymentioning
confidence: 99%
“…1 In Mozambique, it is now the second most incident cancer among Maputo City women, with a crude incidence rate of 8.6/100 000 women. 2 Furthermore, age-standardised mortality rates are greater in low/medium-income than in high-income countries (14.9 versus 11.6/100 000 women, respectively). 1 In sub-Saharan Africa, these differences have been attributed to the high proportion of patients with locally advanced/metastatic disease 3 and to poor access to diagnosis and treatments.…”
Section: Introductionmentioning
confidence: 99%